PUBLIC RELATIONS MANAGEMENT IN BUILDING THE IMAGE OF THE SCHOOL IN MAN 3 MAGETAN - Rahayu, Astri; Ajhuri, Kayyis Fithri (UIN Kiai Ageng Muhammad Besari Ponorogo, 2022)
Abstract: Globalization is currently growing rapidly and has an impact on the sharp competition between educational institutions. One of them is MAN 3 Magetan. MAN 3 Magetan is one of the best aliyah madrasas in Magetan. Evidenced by the many achievements achieved by students and madrasas. MAN 3 Magetan is a madrasa that is increasingly visionary in responding to today's competition. This is considered in the face of sharp competition by paying attention to the positive image of the community to maintain its existence. Therefore the need for public relations management to improve the quality of education, satisfy users and get a good image from the community. This study aims to determine the management of public relations (public relations) at MAN 3 Magetan in building the school's image, to determine the capacity building carried out by public relations at MAN 3 Magetan, and to determine the forms of promotion and cooperation in public relations at MAN 3 Magetan. This study uses a descriptive type of research with a qualitative approach. The data analysis used is Miles & Huberman interactive data analysis, which includes: data reduction, data presentation, and drawing conclusions. The results showed: the stages of public relations management in building an image at MAN 3 Magetan went through three stages, namely planning, implementation, and evaluation. Capacity building carried out by public relations at MAN 3 Magetan is by following the times, namely the holding of skills programs including batik, multimedia, graphic design, light vehicle engineering, fashion, catering, and the existence of a superior program, namely the tahfidz quran. The forms of promotion and collaboration carried out by public relations at MAN 3 Magetan are holding outreach to schools or other institutions, using social media, holding milad, commemorating Islamic holidays (PHBI) and social services. Keywords: Management, Public Relations, Image of Educational Institutions